Mathematical Model for Ship Berthing Allocation in A Multipurpose Terminal: Study Case from Tanjung Perak Port Indonesia - Danendra, Maulana Yafie; Nugroho, Setyo; Mustakim, Achmad (International Journal of Marine Engineering Innovation and Research, 2024)
In the operation of a multipurpose terminal in a port (terminal that can serve and be berthed to more than one type of a ship), the position of planning an optimal berth allocation for ships is essential to maintain. Berth allocation planning (BAP) is considered tactical planning that can impact the performance of a terminal and the cost of a ship in a port. That is because the longer the waiting time of a ship that waits to be berthed, the smaller number of ships will be served by the terminal, and the higher the cost will be borne by the ships. This paper, based on a case study in Terminal Jamrud of Tanjung Perak Port of Indonesia, will discuss a Mixed Integer Linear Programming (MILP) mathematical model of a BAP to minimize the ships’ waiting time to berth with consideration to the tailored conditions of the multipurpose terminal. The results show that the optimization model yielded reductions in the datasets 1 to 3 tested on the North/West and 4 to 6 on the South pier. There are savings in the waiting time reduced in hours, which are 403 (12,82%), 189 (26,18%), 418 (30,74%) for the North/West pier and 34 (16,43%), 1663 (88,13%), 475 (46,75%) for the South pier.